Relative Water Content and Peroxidase Enzyme Activity Lampung Local Rice in the Germination Phase Induced by Polyethylene Glycol 6000 - Putri, Ayu Sasqia; Chrisnawati, Lili; Agustrina, Rochmah; Priyambodo, Priyambodo; Ernawiati, Eti (Metamorfosa: Journal of Biological Sciences; Vol 10 No 2 (2023)DO - 10.24843/metamorfosa.2023.v10.i02.p04, 2023)
Utilizing the potential of local rice is a promising venture in the development of superior drought -resistant rice. One of the local rice that comes from Lampung is the Lumbung Sewu Cantik variety. The purpose of this study was to evaluate the physiological resistance response of Lampung local rice shoots varieties Lumbung Sewu Cantik to the drought stress caused by PEG 6000 through relative water content and peroxidase enzyme activity. This study was conducted using factorial randomized design with 2 factors. Factor 1 is rice varieties (INPAGO 8 (K +), IR 64 (K-), and Lumbung Sewu Cantik). Factor 2 was the concentration of PEG 6000 (0% and 20%). Each treatment combination was repeated 3 times. Data were analyzed for variance and further analysis used DMRT test. The results showed that the drought stress did not have a significant effect on the relative water content of the rice shoots, but had a significant effect on the increase of peroxidase enzyme activity from the rice shoots. The results showed an increase in relative water content (2%) in rice shoots of Lumbung Sewu Cantik variety after being stressed by drought, while both controls experienced a decrease in relative water content. Shoots rice of Lumbung Sewu Cantik variety also experienced the highest increase in peroxidase enzyme activity (0.215 (U / mg)/min) when compared to the two controls. Furthermore, the results of DMRT test at 5% level showed that the activity of peroxidase enzyme activity from rice shoots of Lumbung Sewu Cantik variety was not much different from K- but significantly different from K+. Based on the test results of relative water content and peroxidase enzyme activity, it can be concluded that Lampung local rice, Lumbung Sewu Cantik variety, shows drought tolerance in germination phase and potential to develop into superior drought resistant rice varieties.